Ocular findings in the chronic renal failure - Dahal, P; Gouli, S (Journal of College of Medical Sciences-Nepal, 2015)
BACKGROUND The aim of the study was to evaluate the ocular signs in chronic renal failure (CRF) in diabetes and hypertensive patients. MATERIALS AND METHODS Two hundred and thirty eight cases were enrolled in the study from the nephrology unit of College Of Medical Science, Bharatpur, Nepal and examined in the department of Ophthalmology. The study duration was carried out over 2 years from January 2011 to December 2012. RESULT The number of cases in each grade of CRF were mild 80 (26.67%), moderate 84 (28%), severe 75 (25%), end stage renal disease 61 (20.33%). In all the groups the commonest cause of CRF were Hypertension (HTN) 123 out of 300(41%) and diabetes 98(32.67%). The commonest ocular symptoms in CRF was blurring of vision 68%. CONCLUSION Many important ocular findings like vitreous haemorrage, retinal detachment, neovascular glaucoma and cataract are the presentation in chronic renal failure, which can cause marked vision loss. Hence proper awareness should be provided to the people in time to prevent these ocular complications. DOI: http://dx.doi.org/10.3126/jcmsn.v10i2.12949 Journal of College of Medical Sciences-Nepal, 2014, Vol.10(2); 18-26